RISKS OF THE EDUCATION - R. Aetdinova; Maslova Irina; Niyazbekova Shakizada; Zhakiyanova Zhanna; Saparova Botagoz (Scientific Journal of Pedagogy and Economics, 2021)
The article justifies for the need to identify and to keep track, in practice, of different groups of risks inherent in educational institutions under current conditions of pandemic and post-pandemic transformation of education under the influence of modern world uncertainty. Transformation of education functions in the epoch of digital economy changes the content and types of risks concomitant to the activities carried out by schools. Schools belong to the most conservative types of organizations. However, the environment in which schools operate is constantly changing. An educational institution, as any enterprise, has to engage in the activity aimed at risk management. Manifestation of the risk is, on the one hand, fraught with threats and damage, on the other hand, with opportunities. Assessment of possible threats and risks allows timely projection of undesirable results, creation of a system for situational response to unforeseen circumstances and, in the final analysis, formulation of a strategy for development of the university which would allow achievement of modern high quality education, its fundamentality and conformity to important topical requirements of the personality, society and state. Causes of developing risks characteristic of educational institutions are disclosed. External and internal risks characteristic of educational institutions, sources generating them and the importance of managing them are analyzed. The analysis of risks made reveals multi-varied threats and opportunities in the external and internal environment of the institution and their ability to have a significant effect on educational, organizational and financial activities of the schools.